Case Report: The Different Fates of Three Aneurysms: Diagnosis and Treatment Strategies for Unruptured Intracranial Aneurysms With Other Intracranial Diseases - Guo, Gaochao; Zhao, Liming; Wu, Ruiyu; Xue, Bingqian; Zhang, Shao; Liang, Hao; Gao, Tao; Sun, Yuxue; Liu, Yang; Li, Chaoyue (Frontiers in Surgery, 2022)
Intracranial aneurysms are vascular diseases characterized by local aneurysms of intracranial arteries. Their etiology involves a variety of environmental and genetic factors. Unruptured intracranial aneurysms are more common in intracranial aneurysms, but once an aneurysm is ruptured, the fatality rate and disability rate are extremely high. Therefore, accurate assessment of each step in the detection of intracranial aneurysms, assessment of the risk of rupture, formulation of treatment strategies, and treatment benefits will help to better treat the disease. The current treatment of intracranial aneurysms is limited. Except for surgical intervention, there are no other effective methods. Therefore, when a patient has an unruptured intracranial aneurysm, the formulation of treatment and management strategies is a difficult issue facing neurosurgery. This article introduces the choice of different treatment strategies for 3 patients with intracranial aneurysms complicated with other diseases and reviews the literature.